2016
DOI: 10.18632/oncotarget.10361
|View full text |Cite
|
Sign up to set email alerts
|

Compounds from the marine sponge Cribrochalina vasculum offer a way to target IGF-1R mediated signaling in tumor cells

Abstract: In this work two acetylene alcohols, compound 1 and compound 2, which were isolated and identified from the sponge Cribrochalina vasculum, and which showed anti-tumor effects were further studied with respect to targets and action mechanisms. Gene expression analyses suggested insulin like growth factor receptor (IGF-1R) signaling to be instrumental in controlling anti-tumor efficacy of these compounds in non-small cell lung cancer (NSCLC). Indeed compounds 1 and 2 inhibited phosphorylation of IGF-1Rβ as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…CETSA, a recently developed method to assess drug engagement in complex environments, 28 , 29 builds on the discovery that ligand induced protein thermal shift can also be measured in the context of cell lysates. 43 , 44 , 45 Compared with in vitro assays using recombinant proteins, CETSA keeps target proteins in their native, local environments, maintaining their original post-translational modifications and expression level. Using this method, we found that DHI reduces the thermal stability of IKK α/β , indicating that DHI can interact with IKK α/β in cells.…”
Section: Discussionmentioning
confidence: 99%
“…CETSA, a recently developed method to assess drug engagement in complex environments, 28 , 29 builds on the discovery that ligand induced protein thermal shift can also be measured in the context of cell lysates. 43 , 44 , 45 Compared with in vitro assays using recombinant proteins, CETSA keeps target proteins in their native, local environments, maintaining their original post-translational modifications and expression level. Using this method, we found that DHI reduces the thermal stability of IKK α/β , indicating that DHI can interact with IKK α/β in cells.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds were found to possess antiviral activity and synthetic analogs studies eventually led to the development of cytosine arabinoside (AraC) as a clinically anticancer agent [148]. Eribulin, a truncated synthetic version of halichondrin B, derived from the sponge Halichondria okadai [149], has clinically potential activity against pretreated metastatic breast cancer cells [150,151].…”
Section: From Marine Organisms To Anticancer Drugsmentioning
confidence: 99%
“…Confirmation of target engagement using tool inhibitors and lead optimization intermediates enabled decision making for internal drug discovery programs against diverse target classes including protein deactylase, serine/threonine/tyrosine protein kinase, lysine and arginine N-methyltransferases, oxidoreductase, dioxygenase, and E3 substrate adapter protein family members. Our enthusiasm of the broad applicability of CETSA was buoyed by numerous early reports using the technique to confirm target engagement of individual proteins comprising a wide range of target families [9][10][11][12][13][14][15][16][17][18][19][20][21][22] and the internal development of a mass spectrometry-based platform for thermal proteome profiling of the entire melting proteome. 23,24 We recognized that by replacing the low-throughput, manually intensive Western blot readout originally described with a quantitative, automated, high-density microplate format, we could provide sufficient assay capacity to fully leverage the power of CETSA and embed the technique as an integral part of hit identification and lead generation in early drug discovery campaigns.…”
Section: Introductionmentioning
confidence: 99%